(untitled) (Universal International Scientific Journal, 2026)
This article theoretically analyzes the issue of forming interpersonal socio-psychological influence competencies in students. The socio-psychological influence competency is interpreted as a set of abilities of a person to effectively communicate with others, to consciously and positively influence their thoughts, emotional state and behavior, as well as to correctly perceive external influences. The study sheds light on the scientific foundations of this competency based on social learning, humanistic and systemic approaches. It also analyzes its cognitive, emotional, behavioral and reflexive components, and substantiates that their harmony is an important factor ensuring the social adaptation, psychological well-being and professional readiness of the student.